2016
DOI: 10.1155/2016/1352146
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Isoquinoline Alkaloids, Derived fromMacleaya cordataExtract, on the Development and Innate Immune Response in Swine and Poultry

Abstract: Medicinal extract has been chronicled extensively in traditional Chinese medicine. Isoquinoline alkaloids, extract of Macleaya cordata (Willd.) R. Br., have been used as feed additive in both swine and poultry. Dietary supplementation with isoquinoline alkaloids increases feed intake and weight gain. In addition, recent researches have demonstrated that isoquinoline alkaloids can regulate metabolic processes, innate immune system, and digestive functioning in animals. This review summarizes the latest scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 51 publications
1
26
0
2
Order By: Relevance
“…Similar to the findings with sanguiritrin, administration of MCE for 90 days at doses higher than the daily recommended dosage were well tolerated in rats (Zdarilova et al, 2008). They demonstrated no signs of toxicity and impairment in the health status of the animals, and the remaining alkaloid was unabsorbed and excreted in the feces (Psotova et al 2006), Furthermore, M. cordata was showed up in the European Food Safety Authority (EFSA) database (Ni et al 2016). Previous study demonstrated that dietary supplementation with MCE improved growth performance, gut health, immune systemand digestive function and reduced the diarrhea in nonruminant mammals (Gudev et al 2004;Jankowski et al 2009;Zhang and Coultas 2013;Liu et al 2016).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similar to the findings with sanguiritrin, administration of MCE for 90 days at doses higher than the daily recommended dosage were well tolerated in rats (Zdarilova et al, 2008). They demonstrated no signs of toxicity and impairment in the health status of the animals, and the remaining alkaloid was unabsorbed and excreted in the feces (Psotova et al 2006), Furthermore, M. cordata was showed up in the European Food Safety Authority (EFSA) database (Ni et al 2016). Previous study demonstrated that dietary supplementation with MCE improved growth performance, gut health, immune systemand digestive function and reduced the diarrhea in nonruminant mammals (Gudev et al 2004;Jankowski et al 2009;Zhang and Coultas 2013;Liu et al 2016).…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, the growing broilers fed MCE at 50 and 25 ppm (1-21 d and 22-42 d, respectively) had improved BW and feed conversion rate at 21 d of age (Vieira et al 2008). It has been reported that sanguinarine can regulate the serotonin synthesis by employing tryptophan and finally lead to improvement in feed intake (Ni et al 2016). Improvements in protein retention by reducing intestinal decarboxylation of aromatic amino acids through the inhibition of L-amino acid decarboxylase (Drsata et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, North America, and China, M. cordata is also used to treat skin infections and insect bites (Cai et al, 2016). M. cordata is rich in various alkaloids, including sanguinarine, dihydroderivative, chelerythrine, protopine, allocryptopine, and phenolic acids (Ni et al, 2016;Lin et al, 2018). Ethoxysanguinarine (Eth, Figure 1B) is a product of the transformation of sanguinarine by crystallization of ammoniated ethanol during the extraction process (Konda et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…To defend the organism, the immune system strives to keep challenging agents out (e.g., by tight junction proteins in the intestine), to stimulate inherent immune cells like macrophages, which might eliminate adversary agents by phagocytosis and digestion. The extract of Macleaya cordata is known to support the organism's defence mechanisms, to promote intestinal mucosal growth, to avoid loss of nutrients and to reduce inflammation‐linked blood parameters like haptoglobin (Ni et al, ; Niewold, ). Anti‐inflammatory effects are of high value in case of infections, but the question was, how IQs in feed would work in healthy animals.…”
Section: Discussionmentioning
confidence: 99%
“…R.Br. (Khadem, Soler, Everaert, & Niewold, ; Ni, Martinez, & Guan, ; Xue et al, ). These effects might be caused by the anti‐inflammatory properties of IQs (Niewold, ).…”
Section: Introductionmentioning
confidence: 99%